2020
DOI: 10.3390/en13195141
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Optimization of Gas Pipeline Networks

Abstract: The main goal of this paper is to prove that bi-objective optimization of high-pressure gas networks ensures grater system efficiency than scalar optimization. The proposed algorithm searches for a trade-off between minimization of the running costs of compressors and maximization of gas networks capacity (security of gas supply to customers). The bi-criteria algorithm was developed using a gradient projection method to solve the nonlinear constrained optimization problem, and a hierarchical vector optimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Datasets related to this article can be found through the shared link at https://data.mendeley.com/datasets/g7nb7b9ys7/2, an open-source online data repository hosted at Mendeley Data (Takerhi, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…Datasets related to this article can be found through the shared link at https://data.mendeley.com/datasets/g7nb7b9ys7/2, an open-source online data repository hosted at Mendeley Data (Takerhi, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…Modelling and simulation of natural gas networks have enjoyed wide usage in recent times with many studies aiming to optimise different parameters ranging from a single objective such as the operating cost [45] to multiple operational objectives [46]. The inclusion of natural gas network models in power systems reliability studies has also been suggested by Munoz et al [47] who explains that the methodology became expedient in the wake of increasing construction of combined-cycle power plants in which the gas and electricity systems are linked together for power generation in Spain and other countries.…”
Section: Gas Network Modellingmentioning
confidence: 99%
“…Previously multi-objective ant colony optimization (ACO) technique has been extended to a barrel grid (Arya and Honwad, 2018a). Some of the work on a similar objective was carried out by Chebouba A, 2015;Demissie and Zhu, 2017;Osiadacz and Isoli, 2020. The technique, however, has not been applied to a typical multi-distribution pipeline grid.…”
Section: Review Of Gas Pipeline Optimization Techniquesmentioning
confidence: 99%